2015
DOI: 10.1016/j.neuropharm.2014.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Activation of calcineurin underlies altered trafficking of α2 subunit containing GABAA receptors during prolonged epileptiform activity

Abstract: Fast inhibitory signalling in the mammalian brain is mediated by gamma-aminobutyric acid type A receptors (GABAARs), which are targets for anti-epileptic therapy such as benzodiazepines. GABAARs undergo tightly regulated trafficking processes that are essential for maintenance and physiological modulation of inhibitory strength. The trafficking of GABAARs to and from the membrane is altered during prolonged seizures such as in Status Epilepticus (SE) and has been suggested to contribute to benzodiazepine pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…Fluorescence was captured using an Olympus microscope (BX51WI) with a 60× water objective (NA: 0.9) Olympus objective coupled to an EM‐CCD camera (Ixon; Andor; Eckel et al, ; Muir et al, ; Muir and Kittler, ; Smith et al, ). Excitation was provided by a mercury‐spiked xenon arc lamp (Cairn) or by a metal‐halide lamp (X‐Cite120, EXFO).…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescence was captured using an Olympus microscope (BX51WI) with a 60× water objective (NA: 0.9) Olympus objective coupled to an EM‐CCD camera (Ixon; Andor; Eckel et al, ; Muir et al, ; Muir and Kittler, ; Smith et al, ). Excitation was provided by a mercury‐spiked xenon arc lamp (Cairn) or by a metal‐halide lamp (X‐Cite120, EXFO).…”
Section: Methodsmentioning
confidence: 99%
“…It has long been recognized that benzodiazepines lose their potency as status epilepticus continues and that this is partly due to the internalization of synaptic (gammasubunit) containing GABA(A) receptors [35][36][37]. This involves the activation of NMDA receptors and then calcineurin-dependent internalization of the GABA(A) receptors [38,39]. This process points to three specific treatment approaches.…”
Section: Changes In Gaba(a) Receptorsmentioning
confidence: 99%
“…Other studies have demonstrated that phosphatase inhibition can block activity-dependent GABAR trafficking during SE. 11,25 What is not known is whether the dephosphorylation of the b subunit during SE resulted from a promiscuous process that leads to dephosphorylation of all the receptor's phosphorylation sites or a site-directed process that leads to posttranslational changes at a limited number of phosphorylation sites. To confirm and extend that prior finding, 13 the phosphorylation of the b3 (S408/409) and c2 (S327) subunits was determined after LiPilo-SE of 1-hour duration and KA-SE of 3-hour duration.…”
Section: Phosphorylation-dependent Regulation Of Gabars During Se Is mentioning
confidence: 99%